An introduction to medieval theology - Van Nieuwenhove, Rik (Introduction to religion, 2012)
Medieval theology, in all its diversity, was radically theo-centric, Trinitarian, Scriptural and sacramental. It also operated with a profound view of human understanding (in terms of intellectus rather than mere ratio). In a post-modern climate, in which the modern views on 'autonomous reason' are increasingly being questioned, it may prove fruitful to re-engage with pre-modern thinkers who, obviously, did not share our modern and post-modern presuppositions. Their different perspective does not antiquate their thought, as some of the 'cultured despisers' of medieval thought might imagine. On the contrary, rather than rendering their views obsolete it makes them profoundly challenging and enriching for theology today. This book is more than a survey of key medieval thinkers (from Augustine to the late-medieval period); it is an invitation to think along with major theologians and explore how their thought can deeply challenge some of today's modern and post-modern key assumptions.